INTEGRASI BLUE ACCOUNTING DALAM PENGELOLAAN SUMBER DAYA LAUT BERKELANJUTAN DI KAWASAN PESISIR KABUPATEN BANGKA TENGAH - Wenni Anggita; Elmi Rakhma Aalin; Yanto Yanto; Ulfa Ulfa (JURNAL ILMIAH EDUNOMIKA, 2026)
This study analyzes the integration of Blue Accounting as a strategic approach to sustainable marine resource management in Central Bangka Regency. Blue Accounting is a reporting framework that combines ecological, social, and economic data to improve transparency, accountability, and policy effectiveness. Employing a quantitative method and Partial Least Squares Structural Equation Modeling (PLS-SEM), the study examines three key hypotheses: (1) the impact of data integration on readiness to implement Blue Accounting, (2) the effect of institutional readiness on implementation effectiveness, and (3) the contribution of Blue Accounting to the quality of marine management policies. Results indicate all hypotheses are statistically significant. Multidimensional data integration positively influences implementation readiness (β = 0.417; p < 0.001), while institutional readiness significantly affects effectiveness (β = 0.354; p < 0.001). Furthermore, Blue Accounting contributes to enhanced transparency and improved marine policy quality (β = 0.479; p < 0.001). The findings highlight the importance of integrated data systems and institutional capacity in local marine governance.